Increment of activity of Pd(OH)2/C catalyst in order to improve the yield of high performance 2, 4, 6, 8, 10, 12-hexanitrohexaazaisowurtzitane (HNIW). Issue 11 (2nd November 2017) - Fotouhi-Far, Farshad; Bashiri, Hadis; Hamadanian, Masood; Keshavarz, Mohammad Hossein
ABSTRACT: CL-20 [2, 4, 6, 8, 10, 12-hexanitrohexaazaisowurtzitane (HNIW)] is a well-known high performance explosive. The reductive debenzylation of hexaazaisowurtzitane (HBIW) over supported palladium catalyst produces 2, 6, 8, 12-tetraacetyl-4, 10-dibenzyl-2, 4, 6, 8, 10, 12-hexaazaisowurtzitane (TADB). The effects of precipitation conditions of Pd(OH)2 and the porosity of the activated carbon support on the activity of synthesized Pd(OH)2 /C catalysts in the debenzylation of HBIW are investigated here. The activity of Pd(OH)2 /C catalyst is considerably affected by the porosity of the activated carbon. The surface morphology of the synthesized catalysts is studied by X-ray diffraction (XRD) profile analysis and transmission electronic microscope (TEM). Metal dispersion of Pd(OH)2 /C catalysts is changed by precipitation conditions of Pd(OH)2 .